2009
DOI: 10.1177/0363546509349928
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Osteochondral Lesions of the Talus by Open-Field Autologuous Chondrocyte Implantation

Abstract: The results of autologous chondrocyte implantation in the ankle joint are comparable with those in the knee as demonstrated by the significant clinical improvement, hyaline cartilage repair, and the durability of the results. Integration of both T2 mapping and Magnetic Resonance Observation of Cartilage Repair scoring permitted adequate evaluation of the repair site in the ankle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
91
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 39 publications
5
91
1
3
Order By: Relevance
“…The results of our study are consistent with these findings reflecting a high and stable postoperative outcome in the AOFAS score and patient-derived evaluation. In contrast to other shorter-termed studies, we could not detect age, size, previous intervention or duration of symptoms as influencing factors for the clinical outcome [11,17,19,23]. ACI is a proven sophisticated cell-based technique for cartilage repair.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The results of our study are consistent with these findings reflecting a high and stable postoperative outcome in the AOFAS score and patient-derived evaluation. In contrast to other shorter-termed studies, we could not detect age, size, previous intervention or duration of symptoms as influencing factors for the clinical outcome [11,17,19,23]. ACI is a proven sophisticated cell-based technique for cartilage repair.…”
Section: Discussioncontrasting
confidence: 81%
“…In the longest follow-up found in literature, Giannini et al [17] accounted a series of ten patients (defect size 3.1 cm²) with a follow-up of ten years. The AOFAS score was 37.9 points at baseline, 89.4 points at 12 months, 93.9 at 36 months and 92.7 points at final follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] However, Nam et al 18 did not recommend autologous chondrocyte implantation as an initial treatment option because the investigations on talar lesions were preliminary. Giza et al 17 suggested that matrix-induced autologous chondrocyte implantation into articular defects of the talus is a reasonable revision treatment for osteochondral defects of the talus in patients who do not respond to an initial bone marrow stimulation technique.…”
Section: Discussionmentioning
confidence: 99%
“…ACI is a cell-based, two-stage procedure. In the first procedure, healthy articular cartilage is harvested and the chondrocytes isolated by filtration are cultured for approximately 2 to 3 weeks [34]. In the second step, viable cultured chondrocytes are implanted into the defect site and covered by a periosteal flap harvested from the distal end of the tibia, facilitating a hyaline-like repair tissue.…”
Section: Autologous Chondrocyte Implantationmentioning
confidence: 99%
“…Additionally, it was found that the mean Tegner activity score improved from 1.6 to 4.3. Giannini et al [34] reported clinical and MRI outcomes at a 10-year follow-up following ACI for OLT. The authors evaluated 10 OLT patients with a mean lesion size of 3.1 cm 2 treated with ACI at a mean follow-up of 119 months.…”
Section: Autologous Chondrocyte Implantationmentioning
confidence: 99%